A Case Study Assessing the Auditory and Speech Development of Four Children Implanted with Cochlear Implants by the Chronological Age of 12 Months - Birgit May-Mederake; Wafaa Shehata-Dieler (Case Reports in Otolaryngology)
Children with severe hearing loss most likely receive the greatest benefit from a cochlear implant (CI) when implanted at less than 2 years of age. Children with a hearing loss may also benefit greater from binaural sensory stimulation. Four children who received their first CI under 12 months of age were included in this study. Effects on auditory development were determined using the German LittlEARS Auditory Questionnaire, closed- and open-set monosyllabic word tests, aided free-field, the Mainzer and Göttinger speech discrimination tests, Monosyllabic-Trochee-Polysyllabic (MTP), and Listening Progress Profile (LiP). Speech production and grammar development were evaluated using a German language speech development test (SETK), reception of grammar test (TROG-D) and active vocabulary test (AWST-R). The data showed that children implanted under 12 months of age reached open-set monosyllabic word discrimination at an age of 24 months. LiP results improved over time, and children recognized 100% of words in the MTP test after 12 months. All children performed as well as or better than their hearing peers in speech production and grammar development. SETK showed that the speech development of these children was in general age appropriate. The data suggests that early hearing loss intervention benefits speech and language development and supports the trend towards early cochlear implantation. Furthermore, the data emphasizes the potential benefits associated with bilateral implantation.